2023
DOI: 10.1057/s41599-023-01547-8
|View full text |Cite
|
Sign up to set email alerts
|

Household behavior and vulnerability to acute malnutrition in Kenya

Abstract: Anticipating those most at-risk of being acutely malnourished significantly shapes decisions that pertain to resource allocation and intervention in times of food crises. Yet, the assumption that household behavior in times of crisis is homogeneous—that households share the same capacity to adapt to external shocks—ostensibly prevails. This assumption fails to explain why, in a given geographical context, some households remain more vulnerable to acute malnutrition relative to others, and why a given risk fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Kenya is arguably facing a food insecurity crisis, with an estimated 3.8 million people in rural areas classified as highly to extremely food insecure, and about 4.4 million people projected to experience high levels of acute food insecurity. Overall, 3.1 million people (21% of the analyzed population) are likely to be in crisis, and 1.2 million people (8% of the analyzed population) are in an emergency situation (Bhavnani et al, 2023). The report also highlights that the most affected counties, representing 40% of the total country, are predominantly pastoral livelihoods, such as Isiolo, Turkana, Garissa, Mandera, Marsabit, Samburu, Wajir, and Baringo.…”
Section: Introductionmentioning
confidence: 98%
“…Kenya is arguably facing a food insecurity crisis, with an estimated 3.8 million people in rural areas classified as highly to extremely food insecure, and about 4.4 million people projected to experience high levels of acute food insecurity. Overall, 3.1 million people (21% of the analyzed population) are likely to be in crisis, and 1.2 million people (8% of the analyzed population) are in an emergency situation (Bhavnani et al, 2023). The report also highlights that the most affected counties, representing 40% of the total country, are predominantly pastoral livelihoods, such as Isiolo, Turkana, Garissa, Mandera, Marsabit, Samburu, Wajir, and Baringo.…”
Section: Introductionmentioning
confidence: 98%
“…5,6 In the first half of 2022, Kenya reported 942,000 cases of acutely under-nourished children aged between 6 and 59 months. 7 Under-nutrition is disproportionately distributed based on demographic, social and geographical location. 8 Rural areas have been observed to experience a higher burden; for example, a research study conducted in a rural area of Kenya reported stunting at 26% and 11% underweight children.…”
mentioning
confidence: 99%
“…Prior work operationalizes resilience as a household-level characteristic, capturing the ability of individual households to cope with shocks and stressors. The approach we develop integrates measurements at different units of analysis (Brown et al, 2020;Bakhtsiyarava and Grace, 2021;Grace et al, 2022;Wang and Do, 2023), tracing how household behavior shapes resilience at the ward-level while accounting for feedback loops and nonlinear scaling processes (Béné et al, 2015;Béné, 2020;Bhavnani et al, 2020Bhavnani et al, , 2023. In a given ward, we measure how many children across households fall above/below the malnutrition threshold and to what extent.…”
mentioning
confidence: 99%